Evaluation of Bioactive Compounds and Bioactivities in Plum (Prunus salicina Lindl.) Wine - Liu, Guoming; Wei, Ping; Tang, Yayuan; Pang, Yiyang; Sun, Jian; Li, Jiemin; Rao, Chuanyan; Wu, Cuiqiong; He, Xuemei; Li, Li; Ling, Dongning; Chen, Xi (Frontiers in Nutrition, 2021)
With the increase in demand of fruit wine year by year, it is necessary to develop novel fruit wine with high functional activities. Prunus salicina Lindl. (named as Niuxin plum) is a remarkable material for brewing fruit wine owing to its suitable sugar-acid ratio, characteristic aroma and bioactive compounds. This study intends to modify the fermentation technology, identify and quantify nutritional compositions and volatile profiles, as well as bioactive substances in Niuxin plum wine, as well as evaluate the antioxidant and hypoglycemic activities in vitro of major bioactive components from Niuxin plum wine. According to single-factor and orthogonal tests, the optimal fermentation conditions of 13.1% vol Niuxin plum wine should be Saccharomyces cerevisiae Lalvin EC1118 at 0.1% and a fermentation temperature of 20 °C for 7 days. A total of 17 amino acids, 9 mineral elements, 4 vitamins, and 55 aromatic components were detected in plum wine. Polysaccharides from Niuxin plum wine (named as NPWPs) served as the major bioactive components. The NPWP with a molecular weight over 1000 kDa (NPWP-10) demonstrated extraordinary DPPH free radical scavenging capacity and α-glucosidase inhibitory activity among all NPWPs having different molecular weight. Moreover, the structural characterization of NPWP-10 was also analyzed by high performance liquid chromatography (HPLC), fourier-transform infrared (FT-IR) and nuclear magnetic resonance (NMR) spectra studies. NPWP-10 was composed of mannose, rhamnose, arabinose, galactose and galacturonic acid with molar ratios of 2.570:1.775:1.045:1.037:1. NPWP-10 contained α-configuration as the main component and β-configuration as the auxiliary component. This study highlights NPWP-10 is an importantly biological polysaccharide from Niuxin plum wine, as well as provides a scientific basis for developing the plum wine industry.